"Naturalness" in Designated Wilderness: Long-Term Changes in Non-Native Plant Dynamics on Campsites, Boundary Waters, Minnesota. Issue 1 (28th September 2017) - Eagleston, Holly A; Marion, Jeffrey L
Abstract: Wilderness areas in the United States are preserved for their untrammeled naturalness and opportunities for unconfined recreation. The Boundary Waters Canoe Area Wilderness has these qualities, but long-term recreation visitation pressures on campsites can cause significant ecological changes. This article explores changes on campsites, specifically examining non-native plant ecology over 3 decades. The research replicates a 1982 study analyzing vegetation composition and cover on campsites and environmentally paired controls. Camping activities have removed substantial tree cover on campsites, altering their ecological conditions and perceived wilderness character. Over the span of 32 years, the number of non-native plant species found on campsites has not risen, although their mean relative cover has increased significantly and they have spread to more sites. Of the 23 non-native herbs and grasses found on the campsites, only Cirsium arvense is considered a noxious weed by the state of Minnesota. Other noninvasive, non-native plants fall into a gray area in the context of "naturalness" for an area protected as Wilderness because they provide some positive ecological services even as they degrade wilderness character. Thus, wilderness managers face a difficult challenge in coping with the long-term impacts of visitor use on wilderness conditions and character.